Women's Special Issue Series: Analytical Methods - Samanidou, Victoria; Pino, Verónica; Kalogiouri, Natasa (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
In this Special Issue, seven original research articles, two review articles, and one protocol show the impact of female researchers in the field of analytical science. Analytical methods are necessary in dentistry, medicine (both human and veterinary), archaeology, the pharmaceutical industry, food science and technology, and environmental sciences, and these are only a few examples. The multidisciplinary role of chemistry is reflected in all important advances from research groups in technological progress, proving that analytical chemistry is the key issue in scientific progress. In parallel with this outstanding role of analytical chemistry in a variety of scientific fields, we would particularly like to reflect the impact of female researchers in the field of analytical chemistry in this Special Issue to serve as a motivational guide for girls and women pursuing a STEM career. Therefore, we invited well-established scientists to share the results of their research with the scientific community through this Special Issue, which aimed to compile manuscripts written or lead by women analytical chemists.